2018
DOI: 10.1016/j.foodres.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antioxidant activity and physicochemical properties of yogurt enriched with concentrated strawberry pulp obtained by block freeze concentration

Abstract: Strawberry juice was concentrated using block freeze concentration process. The concentrate was used to produce two yogurts with different concentrations of cryoconcentrated strawberry pulp (15% and 30%). Total lactic acid bacteria count, physicochemical and rheological properties was evaluated during storage (7days) for all yogurts. Also, the beverages produced were compared with two commercial trademarks. It was observed that the total lactic acid bacteria count remained higher than 10CFU·mL during the stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 21 publications
17
85
1
Order By: Relevance
“…The concentrate product obtained can be used to enrich food products. One example, is the use of block freeze concentrated strawberry pulp to enhance the phenolic compounds in yogurts performed by Jaster et al . The authors showed that the product was an excellent alternative for the production of a dairy beverage with high nutritional quality.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrate product obtained can be used to enrich food products. One example, is the use of block freeze concentrated strawberry pulp to enhance the phenolic compounds in yogurts performed by Jaster et al . The authors showed that the product was an excellent alternative for the production of a dairy beverage with high nutritional quality.…”
Section: Resultsmentioning
confidence: 99%
“…Jaster et al . () extracted and quantified TPC from milk from different species. In cows' milk, they found about 5 mg GAE per 100 g of milk.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of bioactive components into yoghurt can improve the health benefits of this dairy product. Several studies have evaluated yoghurt as a potential carrier for antioxidant compounds (Jaster et al 2018). The main bioactive compounds in saffron are crocetin (8,8 0 -diapoc-arotene-8,8 0 -dioic acid) esters, unusually water-soluble carotenoids, the monoterpene aldehydes safranal, the main compound of essential oil of saffron and picrocrocin, the glycoside precursor of safranal.…”
Section: Antioxidant Activity Of Yoghurtmentioning
confidence: 99%
See 1 more Smart Citation
“…The consistency index ( K ), apparent viscosity ( η a , 50 ), and Casson yield stress ( σ ac ) values were significantly decreased with increasing the concentration of UDP from 0.2% to 0.6% (w/v) ( p < 0.05). Similarly, Jaster et al () observed that the K value decreased with increased the concentration of strawberry pulp added to yogurt. Based on these findings, it was indicated that yogurt substituted with UDP (0.2%–0.6%, w/v) was a shear‐thinning fluid and the steady shear rheological properties of yogurt were decreased in comparison with the control.…”
Section: Resultsmentioning
confidence: 80%